IMPLEMENTATION OF STORY-BASED ANIMATED VIDEO TO IMPROVE THE ABILITY TO DISTINGUISH SIMILAR LETTERS AMONG STUDENTS WITH LEARNING DISABILITIES IN AN INCLUSIVE ELEMENTARY SCHOOL - Nur Azmy; Riana Nurhayati (SOSIOEDUKASI, 2026)
This study aims to describe the planning, implementation, and evaluation of story-based animated video in improving the ability to distinguish similar letters (b-d, p-q, n-m) among a special needs student with learning disabilities in grade V of SDN 003 Telen. A descriptive qualitative approach with a single-subject case study design was used. The main subject was a grade V student with a learning disability, with the classroom teacher and parent as supporting data sources and learning documents as additional data. Data were collected through moderate participatory observation, semi-structured interviews, and documentation study, checked for trustworthiness through source and technique triangulation, and analyzed through data reduction, data display, and conclusion drawing. The results show that learning planning was arranged adaptively based on identifying student needs, selecting suitable video media, and designing simple, gradual learning steps. Implementation took place over eight sessions and showed progressive development, from hesitation in early sessions to greater independence and confidence in later sessions. Authentic, ongoing evaluation indicated improvement in distinguishing similar letters, with the b-d pair showing the most consistent progress, while p-q and n-m still required further practice. Beyond cognitive-visual gains, the student also showed affective development in engagement, courage, and learning motivation. The study concludes that story-based animated video is effective as an alternative learning medium for students with learning disabilities because it matches learning needs that are concrete, multisensory, and grounded in meaningful narrative context.